Factors associated with nursing diagnoses in chronic kidney patients: a cross-sectional study - Mercês, André Emanuel Dantas; Marinho, Christielle Lidianne Alencar; Fernandes, Flávia Emília Cavalcante Valença; Carvalho, Evanilda Souza de Santana; Cañon-Montañez, Wilson; Souza da Silva, Rudval (Revista Cuidarte, 2021)
Introduction: To the care plan, the nurses must use the nursing process and adopt their perspectives, cognitive and documentary, considering the human responses of each chronic kidney disease patient, to define the nursing diagnoses, results, and interventions. This study is aimed to analyze the nursing diagnoses of NANDA-I in chronic renal patients and its association with clinical and sociodemographic variables. Materials and Methods: Analytical cross-sectional study, performed with chronic renal patients undergoing hemodialysis. The study population consisted of 177 medical records of chronic kidney disease patients. They were selected in the pre-established period of six months: July to December 2018. It was used the Google Forms® platform to import the data directly to Microsoft Excel® Program by generating an electronic spreadsheet that allowed organizing the data, this was then transcribed to the Stata 14.0 software to perform the statistical analyses. Results: The risk for bleeding diagnosis showed a significant difference with the variable access route (p = 0.02); risk for falls was associated with the variables age, occupation, education (p <0.01) and excessive fluid volume with the variable duration of treatment (p = 0.01). Discussion: In the case of nursing diagnoses, these must be planned and documented based on a standardized nursing language, with NANDA-I. Conclusion: The findings of this study showed the main nursing diagnoses and its association with clinical and sociodemographic variables in chronic renal patients in a Brazilian context. Future research may lead to implement care plans for the most prevalent nursing diagnoses in this type of population. How to cite this article: Mercês, André Emanuel Dantas; Marinho, Christielle Lidianne Alencar; Fernandes, Flávia Emília Cavalcante Valença; Carvalho, Evanilda Souza de Santana; Cañon-Montañez, Wilson; Silva, Rudval Souza da. Factors associated with nursing diagnoses in chronic kidney patients: a cross-sectional study. 2021;12(3):e2160. http://dx.doi.org/10.15649/cuidarte.2160